A study of polymethoxy-1-alkenes in Raphidiopsis (Cylindrospermopsis) raciborskii and Aphanizomenon gracile isolated in Poland. (5th December 2019) - Rzymski, Piotr; Evans, Daniel M.; Murphy, Patrick J.; Kokociński, Mikołaj
Abstract: Previous studies indicated that teratogenic polymethoxy-1-alkenes (PMAs) are produced by phylogenetically diverse cyanobacteria taxa, however corresponding studies on the occurrence of PMAs in European cyanobacteria are lacking. Herein, the presence of PMAs in strains of Raphidiopsis raciborskii and Aphanizomenon gracile isolated from surface waters in Poland was studied using nuclear magnetic resonance and mass spectrometry. No PMAs were detected in any of the strains investigated, indicating that production of these compounds may be geographically diversified. Further studies are necessary to elucidate mechanisms of cyanobacterial PMAs synthesis. Highlights: Polymethoxy-1-alkenes were studied in Polish A. gracile and R. raphidiopsis strains. NMR and mass spectrometry were applied for compound identification. None known teratogenic PMAs were identified in any studied strain. The synthesis of PMAs appears to be strain-dependent/geographically diversified.